Evolution of Management Control Systems in Private Nonprofit Higher Educational Institutions - Panlilio, Purisima P. (LIRIP Journal of Interdisciplinary Studies; Vol 3 (2020): LIRIP Journal of Interdisciplinary Studies, 2021)
This study addresses the use and evolution of management control systems (MCS) in private nonprofit higher education institutions (HEIS) in Pampanga as they undergo stages of development, which involve academic and MCS milestones. The case study method was used in investigating the evolution of MCS in three private nonprofit HEIS. From the results, an MCS transformation model for such HEIS was developed. The research reveals the significant role of evolved MCS in (a) efficiently managing organizational growth; (b) attaining operational quality for better and relevant academic services; (c) fostering empowerment, motivation, and values development among school heads or managers; and (d) promoting the HEIS' capacity development to respond positively to opportunities in their external environment.